Risk of Long COVID in People Infected With Severe Acute Respiratory Syndrome Coronavirus 2 After 2 Doses of a Coronavirus Disease 2019 Vaccine: Community-Based, Matched Cohort Study. (12th September 2022) - Ayoubkhani, Daniel; Bosworth, Matthew L; King, Sasha; Pouwels, Koen B; Glickman, Myer; Nafilyan, Vahé; Zaccardi, Francesco; Khunti, Kamlesh; Alwan, Nisreen A; Walker, A Sarah
Abstract: We investigated long COVID incidence by vaccination status in a random sample of UK adults from April 2020 to November 2021. Persistent symptoms were reported by 9.5% of 3090 breakthrough severe acute respiratory syndrome coronavirus 2 infections and 14.6% of unvaccinated controls (adjusted odds ratio, 0.59 [95% confidence interval, .50–.69]), emphasizing the need for public health initiatives to increase population-level vaccine uptake.